Analisis Waste pada Produksi Arm Sepeda Motor Menggunakan Metode 5S dan Value Stream Mapping di PT XYZ - Mochammad Tomy Santoso; M. Nushron Ali Mukhtar (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2026)
The development of the manufacturing industry at the Small and Medium Enterprises (SMEs) scale in Indonesia demands increased efficiency in the production process to be competitive, but various wastes are still found, especially in non-value-added activities. This study aims to identify, analyze, and minimize waste in the production process of motorcycle Arm spare parts at PT. XYZ. The method used is a Lean Manufacturing approach through the application of Value Stream Mapping (VSM) and 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke). Data collection was carried out through direct observation, interviews, and questionnaires to identify the dominant types of waste using VALSAT (Value Stream Analysis Tools) weighting. The results showed that the main waste that occurred was movement and transportation caused by manual cleaning processes, suboptimal layouts, and inefficient material flow. Current State Mapping analysis showed a total waiting time of 4322 seconds, with activities that still contain waste. After the proposed improvements through Future State Mapping and the implementation of 5S, there was an increase in efficiency with a waiting time of 4260 seconds and an improvement in the condition of the work area to be neater, more organized, and safer. The conclusion of this study shows that the integration of VSM and 5S methods is effective in reducing waste, improving process flow, and increasing productivity and work efficiency in the metal SME industry.